Perkuatan Tanah Gambut Ambarawa dengan Cerucuk Menggunakan Pemodelan Finite Element Method - Chyntia Helmalia Br S. Milala; Dora Melati Nurita Sandi; Mirza Ghulam Rifqi (Journal of Applied Civil Engineering and Infrastructure Technology, 2026)
Peat soils, which are mainly composed of semi-decayed plant remains, usually have high compressibility and low bearing capacity. The high compressibility and low bearing capacity mean that peat soil must be improved if construction is to be built on it. Research was conducted to find a method for soil improvement. Improvements were made by reinforcing the peat with bamboo stakes using the finite element method modeling. In the results of modeling and calculations using software based on the finite element method, the Ambarawa peat soil, before reinforcement with a bamboo stakes at a 5-day time interval, obtained a total deformation value of 7.18 m. After a 5-day interval, the soil collapsed due to its low bearing capacity, preventing further calculations and leaving the safety number unknown. In the Ambarawa peat soil after reinforcement with a bamboo stakes planned 8 m long bamboo stakes and a distance of 1 m between bamboo stakes based on calculations using finite element method modeling at a time interval of 5 days, the total deformation value was obtained at 3.98 m, a time interval of 10 days at 4.46 m, a time interval of 15 days at 4.46 m. Based on the known deformation value, the maximum safety value of this modeling was obtained at a time interval of 30 days, with a value of 1.173.